The secrets of college success - Jacobs, Lynn F., 1955-; Hyman, Jeremy S. (San Francisco : Jossey-Bass, 2010)
'Over 500 essential tips and tricks for current and future students From Lynn F. Jacobs and Jeremy S. Hyman, the authors of Professors' Guide to Getting Good Grades in College, comes this insider's look at what it takes to succeed in college. Written in an engaging and accessible style by two highly experienced college professors, this book is an essential resource for high school students and incoming freshman that includes tips on a variety of topics, such as 6 things to do the summer before college. Do's and don'ts for picking your courses. The 12 habits of top college students. 10 secrets of taking excellent lecture notes. 15 ways to make your professor love you. Find out what college is really about from the people who know it best-the professors.'--
Includes index
Keywords: College student orientation -- United States; College students -- United States -- Conduct of life; College students -- Time management -- United States